Strategic Resources and Firm Performance: An Application of the Resource Based View - Rana Tanveer Hussain; Abdul Waheed (The Lahore Journal of Business)
Under the influence of the framework that defines the Resource Based View, the purpose of this paper is to examine the contribution of the strategic resources (intellectual capital) that create value for the firm. More specifically, we assess the effect of intellectual capital on operating, financial and stock market performance of the firms listed in the personal goods sector of Pakistan Stock Bourse, for the period of 2005 to 2014. The notion of intellectual capital is measured by intellectual capital efficiency, and the “value added intellectual coefficient” method proposed by Pulic (1998), which comprises of capital employed efficiency, human capital efficiency, and structural capital efficiency. The results depict that intellectual capital has a significant, positive effect on operating and financial performance of the firms, while capital employed resources have an insignificant, and mixed effect on operating and financial performance of the firms. This means that the more the firms will accumulate intellectual capital resources, the higher will be their operating and financial performance. Capital employed resources have a significant, positive effect on stock market performance of the firm, and intellectual capital also affects stock market performance, but this relationship is insignificant in nature. The accumulated effect of all the resources (physical & intellectual) shows a positive relationship with the performing areas of the firm in the sector.